Il pensiero come pietas - Trincia, Francesco Saverio (Bollettino Filosofico, 2016)
Starting from Vergilius’ “pius Aeneas”, then going through Emmanuel Lévinas’ Autrement qu’etrê ou au-delà de l’essence and Sigmund Freud Vergängligkeit and Zeitgemässes über Krieg und Tod, my claim is that pietas is opposite to any feeling and to any behaviour of arrogance, and is therefore  the courage to face with faith and  without previous assurances the destiny of decadence that affects in the historical  time all of us and what we feel and appreciate as our values of beauty and of perfection in nature and in culture. For Sigmund Freud in particular, to whom I dedicate most interest and attention in the essay, pietas is the acknowledgement of the value of the eternal beauty which should not be in any way diminished by its being consumed by time and history. In spite of its being precarious in the flowing of the historical time, the value of the beauty things, enjoyed by us in any single moment, is for ever. And this pietas toward the precariousness of natural and cultural beauty is furthermore what assures us that not mourning but hope is the last word of mankind.